Metal ion independent conductance through bis-chelated metal complex molecular wires based on a bis(diphenylphosphino)aniline derivative - Gatto, Marco F; Sangtarash, Sara; Jago, David; Abram, R. Tom; Barrett, Eleanor; Sil, Amit; Koutsantonis, George A; Higgins, Simon J; Robertson, Craig M; Nichols, Richard J; Sadeghi, Hatef; Vezzoli, Andrea (Dalton transactions : an international journal of inorganic chemistry, 2025)
It is becoming increasingly evident that transition metal complexes impart desirable qualities in single-molecule electronics, and testing metallic centres in combination with appropriate ligands is salient to building the next generation of single-molecule devices. Metal-phosphine complexes have been the subject of very few studies, despite their extensive use in other areas of chemistry. In this contribution, we fabricated and studied robust single-molecule junctions using linear bis-chelated ligand-metal-ligand complexes of the type [M(PNP) 2 ]PF 6 (M = Cu( i ), Ag( i ) or Au( i ); PNP = bis(diphenylphosphino)aniline functionalised with methylthio contact groups). The robustness of the devices was evinced by surface-enhanced Raman spectroscopy (SERS) and scanning-tunnelling microscopy break junction (STM-BJ) methods, and the conductance of the devices was found to be independent of the central transition metal. Quantum transport calculations show consistent HOMO-LUMO gaps between the studied complexes in the transmission plots, supporting the experimental findings. This study shows that bis-chelation is a viable approach to the fabrication of stable and robust metal-phosphine devices. Bis(chelated) molecular wires allow fabrication of robust single-molecule junctions and show ion-independent charge transport properties.